ACTN3 genotype in Spanish elite swimmers: No "heterozygous advantage". Issue 3 (14th January 2013) - Ruiz, J. R.; Santiago, C.; Yvert, T.; Muniesa, C.; Díaz‐Ureña, G; Bekendam, N.; Fiuza‐Luces, C.; Gómez‐Gallego, F; Femia, P.; Lucia, A.
Abstract : The aim of the present case‐control study was to examine the association of the ACTN3 R577X genotype with elite swimming status. We compared a group of Spanish (Caucasian) elite swimmers ( n  = 88) with other cohorts of the same ethnic origin, i.e., nonathletic controls ( n  = 343) and other types of athletes who are in both end‐points of the sports performance continuum, i.e., world‐class power ( n  = 119) and endurance male athletes ( n  = 154). Swimmers had a lower odds ratio (OR) of having the RX genotype [1.815, 95% confidence intervals (CI): 0.899–3.664] compared with nonathletic controls, yet the association did not reach statistical significance ( P  = 0.096). Endurance athletes had greater OR of having the XX genotype (OR: 2.88, 95% CI: 1.162–7.135, P  = 0.022), or the RX+XX genotype (OR: 1.903, 95% CI: 1.015–3.567, P  = 0.045) compared with swimmers. No other association was found. In summary, we did not observe an association between the ACTN3 R577X polymorphism and elite swimmer's status, suggesting that any influence of this polymorphism is not of sufficient magnitude as to significantly influence elite swimming performance, at least in Spanish athletes.